Homeless and inadequately housed people in the Brussels-Capital Region - Benoît Quittelier; Nicolas Horvat (Brussels Studies, 2019)
On 5 November 2018, Centre d’appui au secteur de l’aide aux sans-abri organised the fifth census of homeless and inadequately housed people in the Brussels-Capital Region. The results from this census supplement a study which has been ongoing for ten years. This article presents the methodology used and the main trends observed. It also proposes some elements for analysis which could shed light on the evolution of the phenomenon.